2022
DOI: 10.3390/met12111955
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al Content on the Microstructural and Grain Growth Kinetics of Magnesium Alloys

Abstract: In order to control the grain size in thermomechanical processing, the grain growth behavior of hot extruded Mg–xAl–1Zn (x = 3, 6, 9) alloys and their relationship with second phase particles and solutes were investigated. The growth rate of AZ61 is greater than that of AZ31 and AZ91 at 300 °C, 350 °C, 400 °C, and 450 °C under isothermal annealing. The average grain growth exponents n of Mg–xAl–1Zn (x = 3, 6, 9) alloys were 2.26, 2.33, and 2.53 at 300–400 °C, respectively. The deviation from the theoretical va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…The formation of such abnormal sub-grain is supposed to be a lack of coherence in the growing precipitates. The difference is that precipitation is not a precursor to abnormal sub-grain, due to the matrix at annealing temperature is a solid solution in AZ31 Mg alloy and AZ61 Mg alloy [28,52]. Significantly, the substructure does not seem to provide a clear driving force for AGG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of such abnormal sub-grain is supposed to be a lack of coherence in the growing precipitates. The difference is that precipitation is not a precursor to abnormal sub-grain, due to the matrix at annealing temperature is a solid solution in AZ31 Mg alloy and AZ61 Mg alloy [28,52]. Significantly, the substructure does not seem to provide a clear driving force for AGG.…”
Section: Resultsmentioning
confidence: 99%
“…In the body-centred cubic (bcc) metal, abnormal grains with 110 [001] orientation in Fe-Si alloys are obtained by thermomechanical treatment, and the grains with 111 [112] orientation grow faster than others in low-carbon steel [26]. Regarding hcp metals, it has been reported that <11 0>-oriented grains show growth advantages in AZ31 Mg alloy, which will lead to the enhancement of <11 0> type texture [27,28]. Pérez-prado et al [29] reported the predominance of <11 0> recrystallized texture in hexagonal materials and presented <11 0> as a stable orientation of abnormal growth grains in AZ31 Mg alloy.…”
Section: Introductionmentioning
confidence: 99%
“…log D = log k + n log t (4) Equation ( 4) enables us to graphically compute the grain-growth exponent, n. The activation energy for grain growth can be calculated as follows [22][23][24][25]:…”
Section: Introductionmentioning
confidence: 99%